Fractal algorithm for 3D-printed continuous porous scaffold design - Zhao, Zongyue; Chen, Xiaojun (Journal of engineering (Stevenage, England), 2019)
In practice, 3D modelling software, such as UG and Pro/E, are commonly adopted to design porous scaffolds within given contours. However, this manual method is quite time-consuming and complicated with poor adaptability. In this study, a novel facial algorithm is proposed for smart scaffold design. By forming a dendritic fractal network, the second-order uniformity and complete connectivity of pores are guaranteed while considering the axial symmetry of certain orthopaedic implants, and the algorithm is adapted for concave and hollow contour shapes. Through experiments, the stability of the algorithm and the characteristics of the two vital performance indicators, i.e. porosity $P{\rm \; }$P and surface area ratio R, are studied. The results show that P and $R{\rm \; }$R of the generated model are insensitive to the shape of the input model, which proves the stability of authors’ method, and the maximum available porosity reaches 78%, higher than the maximum effective porosity found in the literature.